The Nexus of Whistle-blowing Triangle and Whistle-blowing Intentions on the Pakistani Organizations: Moderating Role of Perceived Organizational Support - Yousaf, Waseem; Sajjad Hussain, Muhammad; Aqdas, Ramaisa; Zaman, Qamar; Zirwa Rana, Fazeyha (International Journal of Psychosocial Rehabilitation, 2020)
From the past few decades, the concept of whistleblowing has become novel in the context of an ethical environment. Thus, the foremost purpose of the existing article is to investigate the role of whistle-blowing triangle such as pressure, rationalization, and opportunity on the intentions of whistleblowing of the employees of Pakistani organizations. The moderating role of perceived organizational support on the above-stated relationships is also included in the aim of the study. The employees of private and government organizations that are situated in Punjab province are the respondents and data were taken by using questionnaires and PLS-SEM was employed to analyze the data. The results indicated that whistle-blowing triangle such as pressure, rationalization and opportunity have a positive association with the while-blowing intentions and perceived organizational support positive and negatively moderates among the above-stated nexuses. These findings are providing the guidelines to the policymakers that they should formulate the policies regarding the whistle-blowing intentions of the employees that may affect the employees’ job satisfaction and organizational performance.